Humans and environments in the most arid place of the world - de Porras, Maria Eugenia (2021)
The Atacama Desert lies between the Pacific coast and the Andes in northern Chile. It is the largest desert in South America and the driest on Earth. Here, annual precipitation is almost zero. The little water that is available depends on the summer rainfall that falls on the Andean mountains. It reaches the desert by runoff and is found within some canyons or by the emergence of groundwater. The presence of life in this extreme environment may seem unimaginable today; however, fossil and archaeological records reveal that plants, animals, and even humans lived in this region during various periods over the last 18,000 years.